2022
DOI: 10.3389/fpls.2022.813686
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the Plant Growth Promotion and Antagonistic Potential of Bacterial Endophytes From Ocimum sanctum Linn. Against Root Rot Pathogen Fusarium oxysporum in Pisum sativum

Abstract: The present study demonstrates plant growth promotion and induction of systemic resistance in pea (Pisum sativum) plant against Fusarium oxysporum f.sp. pisi by two bacterial endophytes, Pseudomonas aeruginosa OS_12 and Aneurinibacillus aneurinilyticus OS_25 isolated from leaves of Ocimum sanctum Linn. The endophytes were evaluated for their antagonistic potential against three phytopathogens Rhizoctonia solani, F. oxysporum f. sp. pisi, and Pythium aphanidermatum by dual culture assay. Maximum inhibition of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 88 publications
(100 reference statements)
1
10
0
Order By: Relevance
“…Endophytic bacteria showing beneficial influence on the growth, development, and protection of plants against diseases facilitates sustainable approaches in agriculture [18][19][20]. Twenty five bacterial strains were screened in various dual culture assays, from which P. aeruginosa PPB3 and A. aneurinilyticus PPB9 were selected for superior antagonistic activity against F. oxysporum [21]. The formation of inhibition zone between the endophyte and the pathogen on agar medium is usually considered as a result of production of antibiotics, pH change and competition for nutrients [22].…”
Section: Discussionmentioning
confidence: 99%
“…Endophytic bacteria showing beneficial influence on the growth, development, and protection of plants against diseases facilitates sustainable approaches in agriculture [18][19][20]. Twenty five bacterial strains were screened in various dual culture assays, from which P. aeruginosa PPB3 and A. aneurinilyticus PPB9 were selected for superior antagonistic activity against F. oxysporum [21]. The formation of inhibition zone between the endophyte and the pathogen on agar medium is usually considered as a result of production of antibiotics, pH change and competition for nutrients [22].…”
Section: Discussionmentioning
confidence: 99%
“…tritici (wheat take-all fungus). (iii) Gupta et al [ 42 ] found a large decrease in the disease mortality of pea plants infected with the fungal phytopathogen Fusarium oxysporum when they were treated with a consortium of endophytic PGPB that produced VOCs and elicited ISR. (iv) Hamaoka et al [ 43 ] noted that the endophytic PGPB Bacillus velezensis KOF112, originally isolated from Japanese wine grapes, inhibited the mycelial growth of the fungal phytopathogens Botrytis cinerea , Colletotrichum gloeosporioides , and Phytophthora infestans (where strain KOF112 synthesized antibiotics and elicited ISR in treated plants).…”
Section: Plant Bacterial Endophytesmentioning
confidence: 99%
“…The genus Aneurinibacillus is a new genus based on the reclassification of the Bacillus brevis and Bacillus aneurinolyticus groups and belongs to the family Paenibacillaceae [1,2]. Members of the genus Aneurinibacillus have a broad range of promising and useful biological functions, such as plant diseases biocontrol [3,4], the biosynthesis of polyhydroxyalkanoates (PHA) [5], lignocellulose biomass degradation [6] and plant-growth promotion [7][8][9]. Aneurinibacillus species have also shown promising potential in terms of resisting multiple heavy metals [10,11].…”
Section: Introductionmentioning
confidence: 99%